Proportional Income Taxation and Risk-Taking - Domar, Evsey D.; Musgrave, Richard A. (Quarterly Journal of Economics, 1944)
I. Summary and conclusions, 388. — Loss offset provisions, 391. — II. The rationale of investment behavior: yield and risk defined, 393; yield and risk of an asset combination, 398; investor's indifference map and investment equilibrium, 402. — III. Taxation without loss offset: effects of the tax on yield and risk, tax sensitiveness, 403; adjustment of asset combination held, 405. popular versions of the argument, 408. — IV. Taxation with full loss offset: effects on yield and risk, 409; total risk and private risk distinguished, 410; adjustment of asset combination held, 411; total risk increased as result of tax, 412. — V. The general case, taxation with variable loss offset: effects of varying tax rate and varying loss offset, 415; adjustment of asset combination to changes in tax rate, with given loss offset, 418; adjustment to changes in loss offset, with given tax rate, 419. — VI. Qualifications, 421.